2018
DOI: 10.1016/j.precamres.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Ocean redox conditions between the snowballs – Geochemical constraints from Arena Formation, East Greenland

Abstract: The emergence of animal ecosystems is largely believed to have occurred in increasingly oxygenated oceans after the termination of the Sturtian and Marinoan glaciations. This transition has led to several hypotheses for the mechanism driving ocean oxygenation and animal evolution. One hypothesis is that enhanced weathering increased oceanic nutrient levels, primary productivity and organic carbon burial, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 98 publications
4
7
0
Order By: Relevance
“…The timing of AOA evolving into marine settings is consistent with the well-established data that suggest atmospheric oxygenation preceded ocean oxygenation ( Scheller et al 2018 ). Regarding deep ocean redox conditions, the earliest evidence for widespread oxygenation of the deep ocean takes the form of trace metal data for a series of temporary “ocean oxygenation events,” starting after the Marinoan “Snowball Earth” ∼635 Ma ( Sahoo et al 2012 ), and continuing through the Ediacaran (635–541 Ma) and Cambrian (541–485 Ma) Periods ( Sahoo et al 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…The timing of AOA evolving into marine settings is consistent with the well-established data that suggest atmospheric oxygenation preceded ocean oxygenation ( Scheller et al 2018 ). Regarding deep ocean redox conditions, the earliest evidence for widespread oxygenation of the deep ocean takes the form of trace metal data for a series of temporary “ocean oxygenation events,” starting after the Marinoan “Snowball Earth” ∼635 Ma ( Sahoo et al 2012 ), and continuing through the Ediacaran (635–541 Ma) and Cambrian (541–485 Ma) Periods ( Sahoo et al 2016 ).…”
Section: Discussionsupporting
confidence: 85%
“…Multiple studies have reported anomalously high δ 34 S values in the Cryogenian Period (Fig. 1; Appendix 1 1), including the Datangpo Formation in South China (Wu et al 2016 and references therein), the Tapley Hill Formation in Australia (Hayes et al 1992;Gorjan et al 2000), the Court and Rasthof formations in Namibia (Hurtgen et al 2002;Gorjan et al 2003), the Bonahaven Dolomite Formation in Scotland (Parnell and Boyce 2017), and the Arena Formation in East Greenland (Scheller et al 2018). Notably, reported superheavy pyrites in these formations all overlie the Sturtian glacial diamictite, leading to the speculation of a potential linkage between the superheavy pyrite and the Sturtian glaciation (Gorjan et al 2000;Hurtgen et al 2002).…”
mentioning
confidence: 99%
“…+26‰, red dash line), commonly known as superheavy pyrite signals (i.e., δ 34 S pyrite > δ 34 S sulfate ). Data source: (1) Tapley Hill Formation (Adelaide Rift Complex), Australia (Gorjan et al 2000); (2) Rasthof, Gruis, and Ombaatjie formations of the Otavi Group, Namibia (Hurtgen et al 2002);(3-14) Datangpo Formation in South China, including localities at (3) Yangjiaping, Hunan Province (Li et al 2012), (4) Tanganshan, Hunan Province (Liu et al 2006), (5) Dawu mine, Songtao County, Guizhou Province (Zhou et al 2007;), (6) Xiangtan, Hunan Province (Li et al 1999a;Liu et al 2006), (7) Zhailanggou mine, Songtao County, Guizhou Province (Chen et al 2008), (8) Yanglizhang mine, Songtao County, Guizhou Province (Zhou et al 2007), (9) Minle mine, Huayuan County, Hunan Province (Tang 1990;Li et al 1999a;Tang and Liu 1999;Feng et al 2010;Li et al 2012;), (10) Lijiawan, Songtao County, Guizhou Province (Wang et al 2016), (11) Xixibao mine, Songtao County, Guizhou Province (Zhang et al 2013;Wang et al 2016), (12) Gucheng, Hubei Province ), (13) Datangpo mine, Songtao County, Guizhou Province (Li et al 1999a;Zhou et al 2007;), ( 14) Daotuo mine, Songtao County, Guizhou Province (Zhu et al 2013;Wang et al 2016); (15) Tapley Hill Formation in the Adelaide Rift Complex, Australia (Gorjan et al 2000); (16) Tapley Hill Formation in the Amadeus Basin, Australia (Gorjan et al 2000); (17) Gobabis Member, Namibia (Gorjan et al 2003); (18) Arena Formation, East Greenland (Scheller et al 2018); (19) Bonahaven Dolomite Formation, U.K. (Parnell and Boyce 2017). All the compiled data are available in the online Appendix 1 1.…”
mentioning
confidence: 99%
“…The Cryogenian non-glacial interlude might be the only period in Earth's history with global occurrence of superheavy pyrite for over ∼10 million years. Superheavy pyrite of this geological interval has been reported from South China [ 11–13 ], Namibia [ 37 ], East Greenland [ 14 ], Scotland [ 38 ], Svalbard [ 39 ], Australia and Canada [ 37 , 40 ] (Fig. 1 A).…”
Section: Geological Record Of Superheavy Pyritementioning
confidence: 68%
“… A compilation of δ 34 S py data showing superheavy pyrite in Earth history. (A) is an expanded view of (B), modified from Canfield and Farquhar [ 16 ], highlighting superheavy pyrite from the Cryogenian non-glacial interval in South China [ 11 , 13 , 21 , 22 ], East Greenland [ 14 ], Australia [ 9 ], Canada [ 9 ], Namibia [ 17 , 37 ], Svalbard [ 39 ] and Scotland [ 38 ]. Seawater sulfate isotope values (δ 34 S sw ), green line in (A), are estimated from sulfur isotopic compositions of evaporates in Australia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%